2016
DOI: 10.1021/acs.jpca.6b02631
|View full text |Cite
|
Sign up to set email alerts
|

Geometrical and Electronic Structures of MnS3–/0 Clusters from Computational Chemistry and Photoelectron Spectroscopy

Abstract: The B3LYP functional and CASPT2 method have been applied to investigate the geometrical and electronic structures of η(2)-(S2)MnS(-/0), η(2)-(S3)Mn(-/0), and MnS3(-/0) isomers of MnS3(-/0) clusters. The ground state of the anionic cluster is computed to be the (5)B2 of η(2)-(S2)MnS(-) isomer, whereas that of the anionic cluster is calculated to be the (4)B1 of the same isomer. The photoelectron spectrum of MnS3(-) cluster is interpreted by electron detachment processes from the most stable η(2)-(S2)MnS(-) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…A more popular approach to investigate the ground and excited states is the multiconfigurational CASSCF/CASPT2 method. In the literature, we can see that the CASSCF/CASPT2 method is applied to study a large amount of transition metal-containing compounds. However, the application of CASSCF/CASPT2 is limited because of the active space. Most of the computational systems can handle CASSCF/CASPT2 calculations with an active space of 14 orbitals, but the active space with 14 orbitals is not enough to get reliable relative energies for the low-lying states of CoGe 2 –/0 and CoGe 3 –/0 .…”
Section: Introductionmentioning
confidence: 99%
“…A more popular approach to investigate the ground and excited states is the multiconfigurational CASSCF/CASPT2 method. In the literature, we can see that the CASSCF/CASPT2 method is applied to study a large amount of transition metal-containing compounds. However, the application of CASSCF/CASPT2 is limited because of the active space. Most of the computational systems can handle CASSCF/CASPT2 calculations with an active space of 14 orbitals, but the active space with 14 orbitals is not enough to get reliable relative energies for the low-lying states of CoGe 2 –/0 and CoGe 3 –/0 .…”
Section: Introductionmentioning
confidence: 99%
“…In such cases, the multiconfigurational CASSCF/CASPT2 method needs to be employed. With the ability to calculate the energies of all of the important ground and excited states with high accuracy, CASSCF/CASPT2 has been known as a sufficient method to investigate the low-lying states of transition metal-containing compounds. Also, the electron detachment energies of the anionic clusters as computed with the CASPT2 method are usually in good agreement with the experimental values as observed in the photoelectron spectra. , To the best of our knowledge, the multiconfigurational CASSCF/CASPT2 method has not been employed to study the geometrical and electronic structures of vanadium-doped germanium clusters.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the open 3d shell of V, VSi 3 –/0 clusters are expected to have complicated geometrical and electronic structures as transition metal containing clusters. In many cases, it is found that several low-lying states are nearly degenerate, and numerous isomers have almost the same stability. , Density functional theory is usually used to study vanadium doped silicon clusters due to the low computational cost. , However, in order to obtain all the relevant low-lying states which are useful to interpret the photoelectron spectroscopy, the multireference CASSCF/CASPT2 method needs to be employed. ,,, Furthermore, to evaluate the relative energy order of the mild multireference electronic states, the ROHF/CCSD­(T) method is used. ,,,, Despite a single-reference method, the CCSD­(T) can give the right relative energy order of the mild multireference electronic states around the minima on the potential energy surfaces. The reason for this feature of the CCSD­(T) method is that, around the minima on the potential energy surfaces, dynamical electron correlation is more important than static electron correlation.…”
Section: Introductionmentioning
confidence: 99%
“…7,16 However, in order to obtain all the relevant low-lying states which are useful to interpret the photoelectron spectroscopy, the multireference CASSCF/CASPT2 method needs to be employed. 20,21,25,26 Furthermore, to evaluate the relative energy order of the mild multireference electronic states, the ROHF/ CCSD(T) method is used. 20,22,23,27,28 this feature of the CCSD(T) method is that, around the minima on the potential energy surfaces, dynamical electron correlation is more important than static electron correlation.…”
Section: Introductionmentioning
confidence: 99%